Pengaruh Variasi Debit Fluida terhadap Daya Mekanik Turbin Pelton dengan 16 Sudu - Yasinta, Syaukaty; Wibowo, Dhimas Satria (Proceedings Series on Physical & Formal Sciences, 2026)
Hydropower Plant (HPP) is one of the renewable energy sources that plays an important role in fulfilling electricity needs, especially in areas with sufficient water flow potential. One of the main components in a hydropower plant is the turbine, and the Pelton turbine is commonly used in high-head conditions with low flow rates. As an impulse turbine, this type converts the kinetic energy of water flow into mechanical energy through the impact between the water jet and the buckets on the turbine. Turbine performance is influenced by several operational parameters, such as inlet water flow rate and nozzle configuration. This study aims to analyze the effect of variations in water flow rate on mechanical power and turbine rotational speed (rpm) in a Pelton turbine with 16 blades. The results show that a flow rate of 40 liters per minute (lpm) provides the best performance, yielding maximum mechanical power of 0.6417 watts at nozzle 1 and 0.6050 watts at nozzle 2. The highest shaft rotational speed is also achieved at this flow rate, namely 107.82 rpm at nozzle 1 and 101.66 rpm at nozzle 2. Nozzle position 1 delivers more optimal performance, likely due to better incoming flow pressure. Based on these results, a flow rate of 40 lpm can be used as a reference for determining ideal operating conditions for the Pelton turbine, thus contributing to improved overall efficiency of the power generation system.